Concepções de educação permanente em saúde difundidas por gestores - Castro, Fernanda Cristina de Abreu Quintela (2014)
In 2004, with the publication of Ordinance number 198 GM / MS , the National Policy for Continuing Education in Health was established and recognized as a SUS´s strategy for health care to training, development and reorganization of practices and services , becoming understood as educational activities based in the questioning of the labor process in health , with the aim of transforming the professional practice and organization of work itself in health institutions . With this understanding, we conducted this study in order to analyze the conceptions of Permanent Education in Health disseminated by managers of health department of the city of Baixo Guandu / ES. This research has exploratory and descriptive research is a qualitative approach. Data collection was conducted through nine interviews with script semi-structured, in order to meet the conceptions of permanent education existing and verify that they correspond to the principles proposed by policy. From the data analysis it was found that managers have different interpretations and low appropriating the concept of permanent education , failing to establish you according to the criteria of the policy, the shares are fragile promoted and present guided by hegemonic models education , and that the main difficulties for the implementation of the strategy relate to the lack of financial resource, support and political interest , professional high turnover and lack of a specific agency for region conduct of policy.